STUDI KOMPARASI METODE EOQ DAN POQ DALAM EFISIENSI BIAYA PERSEDIAAN MATERIAL PAVING BLOCK - Adityawan Sigit (TEKNISIA, 2016)
Construction materials project is one of the businesses in the construction project to provide building materials in setting up a building. Rapid increasing development causing many businesses engaged in the field of construction materials. In its activities, the company is in dire need of accurate, relevant and efficient information. Information is not only needed for decision-making, but also for planning and controlling. One of the most important information is inventory information. Inventory information will determine the survival of the company due to lack of inventory. Therefore, the company needs inventory control calculation, or excess inventory will have direct impact on the survival of the company. This paper has objective of sand material analysis for paving block production. Inventory control and material measures that will be used to analyze are Economic Order Quantity (EOQ) and Period Order Quantity (POQ). The case study in this research is in the company of the paving block Merapi Volcanic Materials Innovation Centre - Islamic University of Indonesia (PIMVM - UII). Object of this research is on the sand material inventory. The data to be processed is the data of volume requirements, the cost of ordering, purchasing and storing of sand material. The data will be processed using the method Inventory Control EOQ and POQ. The result of this research showed the cost of EOQ is Rp. 22.505.098,-, and the cost of POQ is Rp. 44,577,478,-. From the results of these two methods, the difference in the price of sand on the EOQ is 49.5% less expensive than the POQ. It is because the cost of storage on the POQ greater than EOQ so the costs for materials become more expensive. Thus, the optimal inventory control methods in the production of paving blocks PIMVM-UII is EOQ.